Reactions of neutral and cationic diamide-supported imido complexes with CO2 and other heterocumulenes: Issues of site selectivity - Ward, B; Orde, G; Clot, E; Cowley, A; Gade, L; Mountford, P (2005)
Experimental and DFT computational studies of the reactions of the cationic diamide-pyridine-supported methyl tungsten complex [W(NPh)(N3N py)Me]+ (2+) with the heterocumulenes CO 2, CS2, RNCO, and RNCS (R = tert-butyl or aryl) are described, together with comparative studies of the group 5 compounds M(N tBu)(N2Npy)Cl(py) (M = Nb (13) or Ta (14)) and Ta(NtBu)(N2Npy)Me (N2Npy = McC(2-C5H4N)(CH2NSiMe3) 2). In all of the reactions of 2+ the heterocumulene inserted exclusively into a W-Namide bond to give unstable intermediates (isolated for certain isocyanate substrates), which subsequently underwent rearrangement via a 1,3-migration of a SiMe3 group. DFT studies of the reaction of 2+ with CO2 showed that insertion into the W-Me bond is in fact thermodynamically preferred, but that insertion into W-Namide is kinetically more facile. Cycloaddition to the W=NPh bond was neither kinetically nor thermodynamically viable. The reactions between Ta(NtBu)-(N2Npy)Me and CO2 or RNCO in contrast gave complex mixtures, as did those between 13 and 14 and CO2. DFT studies showed that in a neutral but otherwise identical tantalum analogue of 2+ the preference for substrate attack at the M-Namide bond is much less pronounced. Reactions of 13 and 14 with the more sterically discriminating RNCO (R = tBu or p-tolyl) did, however, exclusively afford M-Namide insertion/l,3-SiMe3 migration products, and Nb(NtBu) {MeC(2-C5H4N)(CH2NSiMe3)(CH 2NC(OSiMe3)NtBu)}Cl was structurally characterized. The previously reported reaction of Ti(NtBu)(N 2Npy)(py) with ArNCO (Ar = 2,6-C6H 3iPr2) was re-evaluated and shown to involve an analogous Ti-Namide insertion/1,3-SiMe3 migration reaction, ultimately forming Ti(NtBu){McC(2-C5H4N) (CH2NSiMe3)(CH2NC(N(Ar)-SiMe 3)O)}(py). © 2005 American Chemical Society.